DSP system on a chip for a portable fetal heart rate recorder - Ibrahimy, Muhammad Ibn; Ahmed, Firoz; M. Ali, M. Alauddin; Zahedi, Edmond (2004)
For the above purpose, a portable recorder has been developed by using a PIC17C44 microcontroller development board and a real-time DSP algorithm. The recorder is capable of monitoring the fetal heart rate (FHR) as well as maternal heart rate (MHR) for 24 hours. The DSP system on a chip (SoC) reduces the size and power consumption of the device and the use of the DSP SoC, makes an attractive option in the realization of the recorder. This paper describes the development of the recorder and a proposal of the DSP system on a chip for developing the portable recorder.